Threshold effect or spatial spillover? The impact of agricultural mechanization on grain production - Zhihao Wu; Jingqi Dang; Yipu Pang; Wei Xu (Journal of Applied Economics, 2021)
The increase in agricultural machinery input contribution rate has been the most significant structural change in the input factors of grain production in recent years. In this study, we constructed a threshold regression model and a spatial Durbin model to investigate the threshold effects and the spatial spillovers of agricultural mechanization level on grain production, using panel data of 13 prefecture-level cities in Jiangsu, China, from 2000 to 2016. The results reveal that agricultural mechanization has a single threshold effect on grain yield, and that there is a significant spatial spillover effect of agricultural mechanization on grain yield. This means that the improvement of the mechanization level in one region, will significantly promote the increase in the grain yield in its surrounding regions, due to the cross-regional operation of agricultural machinery.
Keywords: 330; Agricultural mechanization; grain production; spatial spillover; threshold effect